Dispersion compensation in single and multi-channel DWDM using chirped apodized fiber Bragg gratings - Kalkala Balakrishna, Kripa; Murthy Chinnammahalli Ramappa, Gopalakrishna; Palani, Karthik (Bulletin of Electrical Engineering and Informatics, 2025)
Chromatic dispersion (CD) is a key limiting factor in long-haul optical fiber communication, particularly in multi-channel dense wavelength division multiplexing (DWDM) systems, where it introduces signal distortion and inter-symbol interference (ISI). This paper proposes a low-dispersion-offset compensation (LDOC) scheme employing Gaussian-apodized linear chirped fiber Bragg gratings (CFBGs) to enhance dispersion management in single and multi-channel DWDM optical fiber communication systems. Simulations were performed in OptiSystem 7.0 for 10 Gbps single-channel transmission over standard single-mode fiber (SSMF) spanning 110–210 km, and were extended to 4- and 8-channel DWDM systems with a 0.8 nm channel spacing. System performance was evaluated in terms of quality factor (Q-factor), bit error rate (BER), and eye height under varying fiber lengths, input powers, and chirp coefficients. The LDOC-enhanced CFBG achieved a Q-factor of 7.04 with a BER of 9.82×10⁻¹³ for single-channel transmission at 180 km, 13.83 with a BER of 5.57×10⁻⁴¹ for a 4-channel system at 150 km, and 7.56 with a BER of 7.76×10⁻¹¹ for an 8-channel system at 150 km. These results confirm significant improvements compared to conventional CFBGs, demonstrating that the proposed LDOC-based approach is a compact and effective solution for next-generation metro-core, long-haul, DWDM, and 5G/6G optical networks.